2019
DOI: 10.3329/bjb.v48i3.47938
|View full text |Cite
|
Sign up to set email alerts
|

Virus titer as a disease resistance indicator in tomato

Abstract: Tomato leaf curl new Delhi virus, a geminivirus with a wide host range is a contagious pathogen of tomato, which also infects many other crops and weeds. Whitefly (Bemisia tabaci Gennadius), a polyphagous vector, is the agent responsible for its spread on a large scale. The pathogen is responsible for a major reduction in the yield of tomato. Ten commercial cultivars of tomato plant were selected to evaluate the effect of virus titer on crop yield. The yield potential along with other traits of these cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Estimation with qPCR revealed a significant rise in virus titers in cotton plants’ early infection stages of CLCuV. A positive correlation between the severity of symptoms and the virus titer has been well documented for Begomovirus infestations ( Wege 2007 ; Ali et al, 2019 ). We observed that the virus titer was significantly lower or negligible in the advanced stage (enation) of CLCuV infestation.…”
Section: Discussionmentioning
confidence: 84%
“…Estimation with qPCR revealed a significant rise in virus titers in cotton plants’ early infection stages of CLCuV. A positive correlation between the severity of symptoms and the virus titer has been well documented for Begomovirus infestations ( Wege 2007 ; Ali et al, 2019 ). We observed that the virus titer was significantly lower or negligible in the advanced stage (enation) of CLCuV infestation.…”
Section: Discussionmentioning
confidence: 84%